Agnon and Germany: the presence of the German world in the writings of S. Y. Agnon - Becker, Hans-Jürgen; Weiss, Hillel (Bar-Ilan Univ. Press, 2010)
Agnon and the Jewish Renaissance / Andrea Weilbacher -- Gershom Scholem and Shmu'el Yosef Agnon: metamorphoses of a friendship / Gerold Necker -- The bookcase of Dr. Manfred Herbst: S.Y. Agnon's novel Shira and European literature / Astrid Popien -- Tirtza and Hershl in Germany: S.Y. Agnon's In the Prime of Her Life and A Simple Story in the context of the family novel in European Realism / Astrid Popien -- Paralysis during transformation: the representation of German characters in Agnon's novel in Mister Lublin's Store / Detlef Müller -- To hear what life is: Agnon's reception in the German press before and after World War II / Andrea Weilbacher -- The Poland stories: introduction to three Poland stories and comparison of versions / Hillel Weiss -- Or Torah, The miracles of the Sexton of the old Beit Midrash, Be-metzulot -- Historical time and space in S.Y. Agnon's Sippure Polin / Boris Kotlerman -- Decadent and menippean elements in S.Y. Agnon's "Be-ne'arenu u'vizkenenu" / Yehuda Friedlander -- Kabbalistic influences: a look at "Aggadat Ha-sofer" and "Ma'aseh Azriel Moshe Shomer Ha-sfarim" / Elhanan Shilo -- The presence of the Holocaust in Agnon's writings / Hillel Weiss -- Aspects of "Primary Holocaust" in the works of S.Y. Agnon / Yaniv Hagbi